2017
DOI: 10.1021/acs.chemmater.7b00655
|View full text |Cite
|
Sign up to set email alerts
|

S-Shaped Suppression of the Superconducting Transition Temperature in Cu-Intercalated NbSe2

Abstract: ABSTRACT2H-NbSe 2 is the prototype and most frequently studied of the well-known transition metal dichalcogenide (TMDC) superconductors. Widely acknowledged to be a conventional superconductor, its transition temperature to the superconducting state (T c ) is 7.3 K -a T c that is substantially higher than those seen for the majority of TMDCs, where T c s between 2 and 4 K are the norm. Here we report the intercalation of Cu into 2H-NbSe 2 to make Cu x NbSe 2 . As is typically found when chemically altering an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
51
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 42 publications
6
51
0
Order By: Relevance
“…We find that both T c and B C2 (0)decrease significantly in Sn-intercalated NbSe 2 as compared to that of parent phase. This is in line with the results reported by Luoet al [17]on Cu intercalated NbSe 2 though Cu and Sn are electronically different entity. Our preliminary analysis suggests that the suppression cannot be ascribed to strengthening of CDW or increasing of inter-layer distance.…”
Section: Introductionsupporting
confidence: 93%
“…We find that both T c and B C2 (0)decrease significantly in Sn-intercalated NbSe 2 as compared to that of parent phase. This is in line with the results reported by Luoet al [17]on Cu intercalated NbSe 2 though Cu and Sn are electronically different entity. Our preliminary analysis suggests that the suppression cannot be ascribed to strengthening of CDW or increasing of inter-layer distance.…”
Section: Introductionsupporting
confidence: 93%
“…This is associated with the fact that high pressure brings the layers in the unit cell closer together, and facilitates overlap of wave functions of the conduction electrons in the adjacent layers. The T c (6.64 K) of Cr 0.0005 NbSe 2 is found to be less than undoped NbSe 2 single crystal, and similar trend has been reported for various intercalated compounds Fe x NbSe 2 6,38 , NbSe 2 36,40 , Ga x NbSe 2 11 , Pd x NbSe 2 45 , Cu x NbSe 2 12 , (LaSe) 1.14 (NbSe 2 ) 46 pnictides 34,44 at both ambient and pressure.
Figure 1( a ) Temperature dependent of resistivity at various applied hydrostatic pressures from 0 to 8 GPa, ( b ) pressure evolution of onset ( T c onset ) and offset ( T c offset ) superconducting transition temperature from resistivity measurements c) temperature dependent of zero field cooled (ZFC) [closed symbols] and field cooled (FC) [open symbols] dc magnetization at various hydrostatic pressures from 0 to 1.02 GPa.
…”
Section: Resultssupporting
confidence: 80%
“…Niobium diselenide (NbSe 2 ) is one of the most studied layered TMDs which has van der Waals attraction between the layers and it has generated much attention due to interplay of superconducting transition temperature ( T c ) 47 and T CDW 2,810 is around 7 K and 33 K respectively. Anisotropy in TMDs, particularly in NbSe 2 compounds, having the highest T c among TMDs, could be significantly enhanced by introducing foreign atoms or molecules in the interlayer space (intercalation process) 6,9,11,12 . The intercalation ability of these compounds is related to the expected implementation of high temperature superconductivity in the sandwich type structures described by the excitonic mechanism 6,9,13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers prefer to use the effective and mature methods to regulate and control the CDW and the superconducting behavior, such as chemical doping [12][13][14][15][16][17][18] , adopting high pressure [19][20][21][22] , gating 23 and controlling layers of the nanoscale samples. It has been established previously that the intercalation of 3d transition metals (such as Zn, Al, Co, Ni, Fe) into 2H-NbSe2 quickly destroyed the Tc to < 1 K. [24][25] Recently, Cava group has also reported that the intercalation of Cu into 2H-NbSe2 to obtain CuxNbSe2 (0 ≤ x ≤ 0.09) 4 15 . However, they found out the type that Tc is suppressed with doping in this situation is unusual, an S-shaped downtrend was found, with an inflection point near x = 0.03 and a leveling off of the Tc near 3 K at higher doping content.…”
Section: Introductionmentioning
confidence: 99%